Market for Corporate Securities and Building the CALM Portfolio Model - Aleksandrovna Vershinina, Anna; Anatolievna Kiseleva, Irina; Vladimirovich Korotkov, Anatoly; Petrovna Nikolaeva, Tatiana; Petrovna Gorelova, Tamara (International Journal of Engineering and Technology, 2018)
This article attempts to explore the role of the market for corporate securities and build an appropriate portfolio. The main goal of this article is to explore the modern market for corporate securities in Russia. The methods of cognition, retrospective and documentary analysis, as well as synthesis, generalization and systematization were used in this work. The essence and structure of the market for corporate securities were examined in the article, its role was identified, and market instruments and their features were explored. Models of building a securitiesâ€™ portfolio were analyzed. Being the main sector of capital flows, the market for corporate securities establishes a mechanism for distributing and redistributing capital to the most relevant sectors of the economy, working with corporate securities. The investment portfolio is formed using various models. These models are diverse, but the authors decided to select the CALM model of dynamic portfolio management as the most accurate one.Â Â